Rebellious Behaviors in Relation to Personality Traits among University Students - Abdel Razek, Hager Adel; Alsharif , Alaa F.; Alsalhi, Najeh Rajeh (Dirasat: Human and Social Sciences, 2024)
Objectives: This study analyzes the AUKUS alliance, a trilateral security partnership formed on September 15, 2021, involving Australia, the United Kingdom, and the United States in the Indo-Pacific region. It seeks to understand the impact of regional power dynamics on the alliance's establishment, explore its stated goals, and examine member states' motives for participation. Methods: The study uses both analytical and national interest approaches to elucidate key aspects. It operates on the argument that a correlation exists between shifts in the balance of power in the Indo-Pacific region and the formation of the alliance. To accomplish this, the study poses and addresses a series of questions. Results: The study concluded several results, most notably that: The divergence of strategic directions, between the active powers in the region, especially between China and the United States, have brought the two countries into a new stage of confrontation with the aim of protecting their political and economic interests in the Indo-Pacific region. Moreover, "AUKUS" will be an effective instrument to deter any potential Chinese threats towards the stability of the region by strengthening the deterrent capacity of the regional allies of the United States, especially since the alliance has many factors of continuity and survival. Conclusions: Based on the findings, it is recommended to conduct further research on the strategic relationship between China and the United States. This research would shed light on how these dynamics influence their interactions with countries in the Indo-Pacific region and other critical global areas.